Live‐cell PCR and one‐step purification streamline DNA engineering. Issue 3 (15th January 2020) - Lyozin, George T.; Brunelli, Luca
Abstract: In vivo DNA engineering such as recombineering (recombination‐mediated genetic engineering) and DNA gap repair typically involve growing Escherichia coli ( E coli ) containing plasmids, followed by plasmid DNA extraction and purification prior to downstream PCR‐mediated DNA modifications and DNA sequencing. We previously demonstrated that crude cell lysates could be used for some limited downstream DNA applications. Here, we show how live E coli cell PCR and one‐step LiCl‐isopropanol purification can streamline DNA engineering. In DNA gap repair, live‐cell PCR allowed the convenient elimination of clones containing background plasmids prior to DNA sequencing. Live‐cell PCR also enabled the generation of specific DNA sequences for DNA engineering up to 11 kilo base pairs in length and with up to 80 base pair terminal non‐homology. Using gel electrophoresis and DNA melting curve analysis, we showed that LiCl‐isopropanol DNA precipitation removed primers and small, nonspecific PCR products from live‐cell PCR products in only ~10‐minutes. DNA sequencing of purified products yielded Phred quality scores values of ~55%. These data indicate that live‐cell PCR and LiCl‐isopropanol DNA precipitation are ideal to prepare DNA for sequencing and other downstream DNA applications, and might therefore accelerate high‐throughput DNA engineering pipelines.